Surface Wrinkling versus Global Buckling Instabilities in Thin Film‐Substrate Systems under Biaxial Loading: Direct 3D Numerical Simulations. Issue 9 (21st June 2022) - Nikravesh, Siavash; Ryu, Donghyeon; Shen, Yu‐Lin
Abstract: When a thin film bonded to a compliant substrate is subject to in‐plane compressive loading, wrinkles on the thin film may form as a consequence of deformation instability. The specimen geometry may also favor global buckling. In this study, a recently developed computational approach is employed to directly simulate 3D wrinkling and buckling from pre‐instability to post‐instability in a straightforward manner, covering a wide biaxial loading spectrum. The finite element models contain an embedded imperfection with perturbed material properties at the film‐substrate interface. This approach is capable of activating the first and subsequent bifurcation modes, along with the deformation patterns in between. It is demonstrated that, in addition to the temporal evolution of wrinkle patterns, surface wrinkling and global buckling can form simultaneously as the substrate becomes thinner. Wrinkles and buckle can either co‐develop, or the buckling‐induced curvature may help facilitate wrinkle formation depending on the specimen thickness and loading biaxiality. Different wrinkle patterns, such as parallel waveform and checkerboard, can even coexist on the same buckled structure. The state of biaxiality can influence the deformation instability significantly, and each bifurcation point can be traced back to certain abrupt changes in the overall load–displacement response. Abstract : A computational strategy is developed to directly simulate complex surface wrinkles as well as structural buckling of the thin film‐compliant substrate system. The study covers the entire biaxial loading spectrum from pure uniaxial to pure equi‐biaxial compression, and provides mechanistic rationale for concurrent wrinkling and buckling, or transitions of wrinkle configuration mediated by global buckling.